Economic burden of dementia and healthcare costs of demented elderly in Malaysia - Koris, Roshanim (2018)
Worldwide, the ageing population is one of the phenomena that cannot be dismissed because of its great social, economic and cultural challenges to individuals, families and societies. The physical and mental health of the elderly should be society’s main concern. The World Health Organisation (WHO) stated that 23% of chronic non-communicable diseases (NCD) are associated with older people. One of the leading contributors to mental and neurological disorders is dementia. The Alzheimer Disease Report stated that the global costs of treating dementia increased from USD604 billion in 2010 to USD818 billion in 2015, which represents 1.09% of global GDP. These costs are expected to reach USD1 trillion in 2018 and to double by 2030. Malaysia is no exception to this trend and is also experiencing the same phenomenon with the number of the elderly increasing and the prevalence of dementia is expected to rise. The specific objectives of this study are first, to estimate the direct and indirect costs incurred by the elderly with dementia both in the community and institutional settings in Malaysia; and secondly, to examine the economic burden of dementia both on individual and national income bases. The third objective is to investigate the determinants of the total healthcare costs for dementia patients. Using a multi-stage sampling design, this study investigated 2274 elderly from four states in Malaysia which have the highest number of adults aged 60 years and above, namely Johor (South Region), Kelantan (East Region), Perak (North Region) and Selangor (Central Region). The Mini-Mental State Examination (MMSE) score was used to measure the cognitive capability among the elderly. Only the elderly with a score of less than 19 marks were selected for further analysis. They were organised into three categories: mild dementia, moderate dementia or severe dementia. The Cost of Illness (CoI) approach was used to analyse the direct and indirect costs from the community setting. The step-down approach made use of the Clinical Cost Modelling (CCM) Software version 3.0 to estimate the provider costs from an institutional setting. The results revealed that the prevalence of dementia is 17.8%. For each individual, the annual direct and indirect costs are RM12,613, RM14,635 and RM18,730 for mild, moderate and severe cases, respectively. The highest direct cost incurred by the demented elderly as outpatients according to the referred disease is cancer and as inpatients, it is vision problems. For the indirect costs, heart disease is the highest contributor to the cost regardless of whether the demented elderly are outpatients or inpatients. The highest direct cost and indirect cost according to the facilities referred to is when the demented elderly used private medical facilities as outpatients, and government facilities as inpatients respectively. This study also estimates that the total economic burden of dementia was around RM8 billion in 2014, and it represents 0.72% of the Malaysian GDP. In terms of the economic burden to the elderly individually, the study indicates that only 1.2% of the elderly with dementia bear the burden of huge expenditure whereby their out-of-pocket health expenditure exceeded 10% of the household income. Using a two-part model, it was found that household income and education level influence the healthcare cost with a positive relationship. However, age influences healthcare costs with a negative relationship. The number of diseases, the frequency of healthcare visits and admissions also affect healthcare cost. This shows that the demented elderly spend more money on healthcare facilities not because they are old, but because they are suffering from diseases. It is hoped that this study will rise up the issues of dementia as a priority in public health and social care in Malaysia. Appropriate actions to prevent dementia and other diseases are needed to ensure good physical and mental health of the elderly population. Financial assistance is essential to avoid the elderly from experiencing catastrophic health expenditure. The main impact of this study is the hope that the economic burden and the healthcare costs among the demented elderly in Malaysia could be minimised. Subsequently, the national vision to generate healthy, successful and productive ageing can be better achieved.